Handbook of Seed Technology for Genebanks: Volume I: principles and methodology - Ellis, R.H.; Hong, T.D.; Roberts, E.H.; International Plant Genetic Resources Institute (1985)
This first volume of seed technology for genebanks deals with many of the principles of seed testing which need to be understood when monitoring the viability of seed accessions maintained in genebanks. It is the second in a general series of genebank handbooks. (Reprinted 1989)